Spatializing blackness: architectures of confinement and Black masculinity in Chicago - Shabazz, Rashad (The new Black studies series, 2015)
"Over 277,000 African Americans migrated to Chicago between 1900 and 1940, an influx unsurpassed in any other northern city. From the start, carceral powers literally and figuratively created a prison-like environment to contain these African Americans within the so-called Black Belt on the city's South Side. A geographic study of race and gender, Spatializing Blackness casts light upon the ubiquitous--and ordinary--ways carceral power functions in places where African Americans live. Moving from the kitchenette to the prison cell, and mining forgotten facts from sources as diverse as maps and memoirs, Rashad Shabazz explores the myriad architectures of confinement, policing, surveillance, urban planning, and incarceration. In particular, he investigates how the ongoing carceral effort oriented and imbued black male bodies and gender performance from the Progressive Era to the present. The result is an essential interdisciplinary study that highlights the racialization of space, the role of containment in subordinating African Americans, the politics of mobility under conditions of alleged freedom, and the ways black men cope with--and resist--spacial containment. A timely response to the massive upswing in carceral forms within society, Spatializing Blackness examines how these mechanisms came to exist, why society aimed them against African Americans, and the consequences for black communities and black masculinity both historically and today"--